Client collection and relationship process of advertising agency in Bangladesh: a case of Rectangle Communications Ltd. - Faruk, Omar (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.